xy + 2x - y = 5
=> x(y + 2) - y - 2 = 5 - 2
=> x(y + 2) - (y + 2) = 3
=> (x - 1)(y + 1) = 3
=> x - 1 va y + 1 thuoc U(3) = {-1; 1; -3; 3}
ta co bang :
x-1 | 1 | -1 | 3 | -3 |
y+2 | 3 | -3 | 1 | -1 |
x | 2 | 0 | 4 | -2 |
y | 1 | -5 | -1 | -3 |
kl_
( Chỉ bt lm theo dạng toán lp 6 thui thông cảm )
xy + 2x - y = 5
x( y + 2 ) - y = 5
=> x(y+2) - y - 2 = 5 - 2
<=> x(y+2) - ( y+2 ) = 3
<=> (y+2) ( x - 1 ) = 3
=> \(\left(x-1\right)\inƯ\left(3\right)=\left\{\pm1;\pm3\right\}\)
( Tự lm tiếp đến đây thì dễ òi )